Prospective study of bezafibrate for the treatment of primary sclerosing cholangitis. (21st August 2015) - Mizuno, Suguru; Hirano, Kenji; Isayama, Hiroyuki; Watanabe, Takeo; Yamamoto, Natsuyo; Nakai, Yousuke; Sasahira, Naoki; Tada, Minoru; Omata, Masao; Koike, Kazuhiko
Abstract Background Primary sclerosing cholangitis (PSC) is a chronic cholestatic disease. Medical treatments must be devised to avoid or postpone liver transplantation in PSC patients. No clinical trial has prospectively explored the efficacy of bezafibrate in PSC patients. Methods We conducted a prospective study of 12‐week bezafibrate treatment, with pre‐ and post‐treatment observation periods, in PSC patients. Bezafibrate was prescribed at 200 mg b.i.d. The primary endpoint was defined as improvements in liver function test (LFT) data after bezafibrate treatment. Changes in LFT data during the study period were assessed every 6 weeks. Results Fifteen patients were enrolled as planned, and 11 completed the study protocol. Biliary enzyme levels improved in all patients after bezafibrate treatment for 12 weeks. Hepatic enzyme levels improved in only seven of the 11 patients, and the efficacy of bezafibrate in PSC patients was thus 64%. LFT data (alkaline phosphatase and alanine aminotransferase levels) were reduced after bezafibrate treatment (both P < 0.05 by Wilcoxon's signed‐rank test), and both significantly increased after bezafibrate cessation (both P < 0.01). Conclusions Bezafibrate effectively improved LFT data in 64% of PSC patients. This is the first prospective clinical trial to evaluate the effect of bezafibrate in PSC patients.